‘URF SEBAGAI METODE PENETAPAN HUKUM EKONOMI ISLAM - Amalia, Khikmatun (AS-SALAM, 2020)
This article aims to discuss matters related to 'urf as a method of determining Islamic economic law in economic activity. The research methodology in this article uses a qualitative method with a library research approach. The results showed that urf is something that is known and has become a community habit, either in the form of words or deeds. So that 'urf can be used as a method of determining Islamic economic law, including in economic transaction activities. Some examples of the application of 'urf in economic transactions today are buying and selling in modern shopping centers and online-based transactions without saying shighat (my words sell-I buy).